Associations Between Body Composition, Leptin, and Vitamin D Varied by the Body Fat Percentage in Adolescents - Khwanchuea, Rapheeporn; Punsawad, Chuchard (Frontiers in Endocrinology, 2022)
Background Serum leptin levels reflects one’s degree of obesity and can affect vitamin D levels. The relationship between body fat, leptin, and 25-hydroxyvitamin D (25(OH)D) has not been extensively studied in adolescents. This study aimed to investigate the correlations between body composition and leptin and 25(OH)D levels in boys and girls. Methods Participants aged 12–14 years (n = 205) were grouped according to sex. After body composition was recorded using bioelectrical impedance analysis, they were classified into three groups according to body fat percentage (%BF) (< 30, ≥ 30 and < 40, and ≥ 40). Serum leptin and 25(OH)D levels were measured using the enzyme-linked immunosorbent assay (ELISA). Correlations between all variables were analyzed according to sex and the percentage of BF groups. Results Boys and girls with %BF ≥ 30 showed no difference in body mass index (BMI), %BF, and leptin and 25(OH)D, while other variables of body composition were more common in boys than in girls. The %BF, body fat mass (BFM), and 25(OH)D of both sexes with %BF ≥ 30, and leptin levels of boys with %BF ≥ 40 increased with an increase in %BF. A negative correlation between leptin and 25(OH)D levels was found in boys with %BF < 40 and girls with %BF < 30. In the %BF ≥ 30 and < 40 groups, there were negative correlations between leptin, BFM, free fat mass, and muscle mass (MM); between leptin, 25(OH)D, and height in boys; and between 25(OH)D, body weight, BMI, and MM in girls. Conclusion A negative correlation between leptin and 25(OH)D levels varied according to sex, while for body composition, it was evident at 30 and 40% BF.